Why Do Sectoral Employment Programs Work? Lessons from WorkAdvance - Katz, Lawrence F.; Roth, Jonathan; Hendra, Richard; Schaberg, Kelsey (Journal of Labor Economics, 2022)
This paper examines the evidence from randomized evaluations of sector-focused training programs that target low-wage workers and combine up-front screening, occupational and soft-skills training, and wraparound services. The programs generate substantial and persistent earnings gains (12%–34%) following training. Theoretical mechanisms for program impacts are explored for the WorkAdvance demonstration. Earnings gains are generated by getting participants into higher-wage jobs in higher-earning industries and occupations, not just by raising employment. Training in transferable and certifiable skills (likely underprovided from poaching concerns) and reductions of employment barriers to high-wage sectors for nontraditional workers appear to play key roles.